2020
DOI: 10.15408/kauniyah.v13i1.13348
|View full text |Cite
|
Sign up to set email alerts
|

Tumbuhan Khas di Kawasan Candi Muaro Jambi Dalam Kajian Etnobotani dan Potensi Ekonomi

Abstract: AbstrakJambi memiliki lahan gambut dan hutan yang cukup luas yaitu sekitar 2 juta ha, sehingga Jambi memiliki biodiversitas yang cukup tinggi, termasuk tumbuhannya. Tumbuhan yang ada di Jambi memiliki kekhasan ciri historis dan ekologisnya, salah satunya di kawasan Candi Muaro Jambi. Tumbuhan tersebut dimanfatkan masyarakat untuk berbagai kebutuhan, namun pengetahuan tersebut mulai hilang dan ditinggalkan, sehingga perlu dikaji dari segi etnobotani dan ekonomi agar tetap dijaga kelestariannya. Penelitian ini b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some of these plants are used together for their benefits. The medicinal plants recognized in this study were also reported to be used by other ethnic groups such as C. speciosus and E. fluctuans by the Serampas community (Hariyadi & Ticktin, 2012); K. pinnata in the Sakai community (Wulandari et al, 2014); and Ceiba petandra by the people in Candi Muaro Jambi area for the same medicinal purpose (Susanti et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…Some of these plants are used together for their benefits. The medicinal plants recognized in this study were also reported to be used by other ethnic groups such as C. speciosus and E. fluctuans by the Serampas community (Hariyadi & Ticktin, 2012); K. pinnata in the Sakai community (Wulandari et al, 2014); and Ceiba petandra by the people in Candi Muaro Jambi area for the same medicinal purpose (Susanti et al, 2020).…”
Section: Discussionsupporting
confidence: 55%
“…The Anak Dalam Tribe (SAD) is a traditional tribe in the province of Jambi, Indonesia, who live in the forests and rely on forest products, including non-timber forest products (NTFPs), to meet their daily needs (Mustakim et al, 2023;Susanti et al, 2020;Ulfa & Mitaria, 2019). One of the well-known local souvenirs of the SAD is accessories made from the skin of the seed of the sebalik sumpah tree.…”
Section: Introductionmentioning
confidence: 99%
“…One of the well-known local souvenirs of the SAD is accessories made from the skin of the seed of the sebalik sumpah tree. Although initially only utilized by the SAD community in Jambi, these accessories are now distinctive souvenirs from the Muaro Jambi Temple area (Susanti et al, 2020). These accessories serve as unique adornments worn in the daily lives of SAD members and depict their local wisdom and close relationship with nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information about the land forest fires and their release of atmospheric pollution, mainly in the lower Batanghari River landscape, is very important and required immediately. This is considering that the lower Batanghari River landscape has intact lowland rainforest with its vast biodiversity that needs to be conserved (Susanti et al 2020;Tamin et al 2019). While at the same time, the landscape is threatened due to deforestation, land-use conversion, plantation expansion, slash and burn practices that have all led to the increase in land fires (Vadrevu et al 2019).…”
Section: Introductionmentioning
confidence: 99%